2014
DOI: 10.1007/s13197-014-1635-9
|View full text |Cite
|
Sign up to set email alerts
|

Powder lemon juice containing oligosaccharides obtained by dextransucrase acceptor reaction synthesis and dehydrated in sprouted bed

Abstract: Oligosaccharides can be synthesized using the sugars present in the fruit juices through the dextransucrase acceptor reaction. In the present work, the effect of reducing sugar and sucrose concentration on oligosaccharide formation in lemon juice was evaluated through response surface methodology. The oligosaccharide formation in lemon juice was favored at high concentrations of sucrose (75 g/L) and reducing sugar (75 g/L). At this synthesis conditions, an oligosaccharide concentration of 94.81 g/L was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…High amounts of oligosaccharides were formed in all experimental runs. Similar results were reported by da with cashew apple juice; and Coelho et al (2014) with lemon juice as substrate. The daily dose of prebiotic oligosaccharide is a controversial issue and different recommended daily intake is reported elsewhere.…”
Section: Pineapple Juicesupporting
confidence: 88%
“…High amounts of oligosaccharides were formed in all experimental runs. Similar results were reported by da with cashew apple juice; and Coelho et al (2014) with lemon juice as substrate. The daily dose of prebiotic oligosaccharide is a controversial issue and different recommended daily intake is reported elsewhere.…”
Section: Pineapple Juicesupporting
confidence: 88%
“…Topspin v.3.2 (Bruker) software was used for processing and analyzing the NMR spectra. The chemical shifts of 1 H (δ H ) and 13 C (δ C ) were referenced to acetone (δ H 2.225 and δ C 31.55, respectively).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The multiplicity-edited HSQC spectrum (Figure 4C) was used to assign corresponding 13 C signals. The downfield shift of C2 signals of the reducing residue indicated that the third glucosyl residue is attached to the reducing residue of maltose via the α-(1→2) linkage, forming a branched structure.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The oligosaccharides synthesis in acerola juice was developed according to the protocol previously established by our group using the enzyme dextran-sucrase Coelho et al, 2015). The synthesis was carried out at the optimum enzyme conditions (30°C and pH 5.2) in a reactor containing 3L of acerola juice.…”
Section: Oligosaccharides Synthesis In the Acerola Juicesmentioning
confidence: 99%